Suitability Evaluation of the Water-Energy-Food System: A Case Study in Sichuan Province, China - Xu, Peng; Wu, Shiqiang; Zhang, Jianmin; Wu, Xiufeng; Jia, Benyou; Dai, Jiangyu; Yu, Lei; Zhang, Yu; Qi, Yongfei (Frontiers in Environmental Science, 2022)
Water, energy and food are the basic resources on which human beings depend for survival and development. However, these resources, ecosystem, society and economy interact with each other in highly complex and interlinked ways, i.e., water-energy-food (WEF) nexus, which is difficult to evaluate quantitatively. In particular, whether there is a harmonious, matching and benign interaction in the WEF system for a given spatial and temporal scale, that is, the WEF system suitability. Thus, we develop a comprehensive model for the WEF system suitability evaluation, which includes stability, coordination and sustainability. The model mainly contains the index system construction, weight calculation and TOPSIS evaluation method. Specifically, we propose an improved weight calculation method (i.e., network assignment method) based on the network analysis method and Amal’s method. A case study in Sichuan Province, China, has shown that: (a) the overall level of the WEF system suitability in Sichuan Province is above medium and shows a fluctuating trend; (b) in terms of the proportion of each indicator to the total, the contribution of coordination indicators to the comprehensive evaluation decreases slightly, and the contribution of sustainability indicators is greater, but the three remain in a balanced state, as evinced by good underlying conditions and potential for future development; (c) the network assignment method can obtain more suitable statistical characteristics (standard deviation, mean, maximum and minimum) compared with the Entropy method, Amal’s method and analytic network process method, which are consistent with the actual conditions in the study area. In general, the evaluation results obtained by the network assignment method can better characterize the nexus at the core of complex multi-resource systems, and have significant advantages in the application of comprehensive evaluation of the suitability of WEF systems.